2010
DOI: 10.1158/1078-0432.ccr-09-2318
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies in Head and Neck Cancer: Understanding Resistance to Epidermal Growth Factor Receptor Inhibitors

Abstract: The epidermal growth factor receptor (EGFR) is a validated target in squamous cell carcinoma of the head and neck (HNSCC). However, despite high expression of EGFR in these cancers, EGFR inhibitor monotherapy has only had modest activity. Potential mechanisms of resistance to EGFR-targeted therapies involve EGFR and Ras mutations, epithelial-mesenchymal transition, and activation of alternative and downstream pathways. Strategies to optimize EGFR-targeted therapy in head and neck cancer involve not only the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 56 publications
(66 reference statements)
0
84
0
Order By: Relevance
“…This is in accordance with reports in the literature on the development of resistance to TKIs in HNSCC in which tyrosine kinase mutations of Egfr are rare events. 28 Cancer cells become resistant to EGFR targeted therapies through several mechanisms. The nature of the gefitinib resistance in the SCCF1G cell line in this study is not known, but some of the previously reported mechanisms of resistance could be consistent with an apparent resistance to tyrosine kinase inhibition but not to siRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with reports in the literature on the development of resistance to TKIs in HNSCC in which tyrosine kinase mutations of Egfr are rare events. 28 Cancer cells become resistant to EGFR targeted therapies through several mechanisms. The nature of the gefitinib resistance in the SCCF1G cell line in this study is not known, but some of the previously reported mechanisms of resistance could be consistent with an apparent resistance to tyrosine kinase inhibition but not to siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired resistance to TKI monotherapy commonly develops over time, 28 so a gefitinib resistant cell line (SCCF1G) was developed and the tyrosine kinase region was re-sequenced, but no mutations were found. Using proliferation assays, the SCCF1G cell line showed no significant inhibition of proliferation at the 5 μM drug dose (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Cal 33 microtumors that were harvested from 300-mm PEGDMA hydrogel microarray devices after 4 days in culture were treated -EGF (50 ng/mL) for 15 min and fixed in paraformaldehyde and stained with Hoechst. The fixed microtumors were then permeabilized in 95% ice-cold methanol, and then the total ERK1/2 or phopspho-ERK1/2 expression levels were determined by indirect immunofluorescence antibody staining, image acquisition on the IXM, and image analysis using the MWCS module (Fig.…”
Section: Activation and Inhibition Of Egf Pathway Activation In Cal 3mentioning
confidence: 99%
“…These fall into two categories. First, resistance may develop via constitutive activation of growth caused by changes in effectors of the EGFR signal transduction pathway (23)(24)(25)(26). Second, proliferation may be stimulated by activation of receptors other than EGFR (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%